2015
DOI: 10.1016/j.neulet.2015.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Examining the association between Apolipoprotein E (APOE) and self-reported sleep disturbances in non-demented older adults

Abstract: We aimed to examine the association between apolipoprotein E (APOE) and sleep disturbances. This is a cross-sectional study, from the Washington Heights-Inwood Community Aging Project (WHICAP). A total of 1,944 non-demented older adults took part in the study. Sleep dysfunction was measured using sleep categories derived from the RAND Medical Outcomes Study Sleep Scale. Genetic association between APOE-ε4 genotype and sleep disturbances was assessed using unadjusted linear regression models. Secondary analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
1
10
0
2
Order By: Relevance
“…APOE genotype status was determined by restriction enzyme isotyping 23 . One individual with an ε2ε4 profile was not included in the sample because the ε2 allele has been shown to have a protective effect on developing AD 24 and is, therefore, thought to neutralize the effect of the ε4 allele 25 .…”
Section: Methodsmentioning
confidence: 99%
“…APOE genotype status was determined by restriction enzyme isotyping 23 . One individual with an ε2ε4 profile was not included in the sample because the ε2 allele has been shown to have a protective effect on developing AD 24 and is, therefore, thought to neutralize the effect of the ε4 allele 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Naps longer than 60 minutes were associated with a greater AD risk among Ɛ4 carriers but not noncarriers, and there was evidence that short naps were associated with reductions in risk of incident AD in both groups. 34 Further, Tsapanou et al 35 reported that Ɛ4 genotype was associated with self-report measures of SDB-related phenomena (snoring, shortness of breath during sleep/ headache on waking) but found no associations with measures of sleep quality or adequacy or of daytime sleepiness. In a particularly relevant recent pilot study (n = 31), Drogos et al 36 found that Ɛ4 carriers had poorer sleep efficiency, as measured by actigraphy and polysomnography (PSG) and shorter sleep duration and greater wake after sleep onset and REM sleep, measured by PSG, than noncarriers; they detected no associations, however, of APOE Ɛ4 status with self-reported sleep measures.…”
Section: Discussionmentioning
confidence: 99%
“…In the present data, we present the details of the cross-sectional study that examined the association between Apolipoprotein E ( APOE -ε4) and snoring/sleep apnea in a large group of older adults. We provide the demographic characteristics of our sample, the frequencies of the APOE alleles in our population, the sleep scale we used, and the results of the association analyses between APOE -ε4 and sleep variables stratified by ethnic group [1] .…”
Section: Data Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Stratified analyses were conducted in order to examine the association between APOE -ε4 and sleep variables by ethnic group. For further analyses and enhanced discussion, see “ Examining the association between Apolipoprotein E (APOE) and self-reported sleep disturbances in non-demented older adults ” by Tsapanou et al (2015) [1] .…”
mentioning
confidence: 99%